2021
DOI: 10.1038/s41436-020-00946-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing rare variant interpretation in inherited arrhythmias through quantitative analysis of consortium disease cohorts and population controls

Abstract: Stringent variant interpretation guidelines can lead to high rates of variants of uncertain significance (VUS) for genetically heterogeneous disease like long QT syndrome (LQTS) and Brugada syndrome (BrS). Quantitative and disease-specific customization of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 21 publications
0
71
0
2
Order By: Relevance
“…A research suggested that pathogenic variants in KCNH2 encoding may result in Long QT syndrome 47 . Meanwhile, another research based on quantitative analysis of consortium disease cohorts and population controls pointed out among patients with long QT syndrome, the mutation probability of KCNH2 gene is greater than 85% 48 . Besides, another research mentioned the co-expression of CACNA1C and KCNH2 reduces the arrhythmic events 49 .…”
Section: Discussionmentioning
confidence: 99%
“…A research suggested that pathogenic variants in KCNH2 encoding may result in Long QT syndrome 47 . Meanwhile, another research based on quantitative analysis of consortium disease cohorts and population controls pointed out among patients with long QT syndrome, the mutation probability of KCNH2 gene is greater than 85% 48 . Besides, another research mentioned the co-expression of CACNA1C and KCNH2 reduces the arrhythmic events 49 .…”
Section: Discussionmentioning
confidence: 99%
“…While this study provides important insights on the relationship between genotype and phenotype in BrS, our understanding of these associations is still rudimentary. For the interpretation of SCN5A variants, a generic classification tool was applied – while the majority of variants were likely to have been correctly classified, gene-specific approaches using high throughput functional assays 14 or quantitative case-control approaches 15 may lead to improved classification and estimation of variant effect size rather than binary predictions. Limited phenotypic differences were observed in this cohort based on SCN5A variant classes and properties - a larger baseline (though not ajmaline-induced) substrate was noted for patients with non-missense variants but there were no significant differences based on topographical location.…”
mentioning
confidence: 99%
“…Previous research suggested that pathogenic variants in KCNH2 encoding may result in long QT syndrome [ 46 ]. Meanwhile, another research based on quantitative analysis of consortium disease cohorts and population controls pointed out that, among patients with long QT syndrome, the mutation probability of the KCNH2 gene is greater than 85% [ 47 ]. Besides, another research mentioned the coexpression of CACNA1C and KCNH2 reduces the arrhythmic events [ 48 ].…”
Section: Discussionmentioning
confidence: 99%